Fearn v Tate Galleries: Privacy and the law of nuisance. (March 2021) - Lees, Emma
This note considers the decision of the Court of Appeal in Fearn v Tate Galleries. It considers the Court's decision specifically with regards to whether the law of private nuisance discloses an action in pure overlooking cases. It argues that as a matter of historical precedent, the Court of Appeal is correct in assessing that the weight of authority argues against such an action. It then analyses how the Court of Appeal's reasoning can be viewed from the lens of understandings of property and ownership, and as part of the discussion of the interaction between planning and private law.